Nouvel essai sur l'évolution de la géographie humaine Espace, sciences sociales et philosophie - Claval, Paul (Sp@tialités, 2022)
Relying on Carl Ritter's analysis of position and on evolutionism, human geography in its classical form stressed long duration and the way men developed modes of life in order to subsist on their environment. It did not focus on cities and the role of distance, even if they were parts of its agenda: they were explored by the New Geography of the fifties and sixties. The discipline becomes then closer to other social sciences and shared the crises they went through. The poststructuralist geography drew from Foucault's analysis of discursive formations and Bourdieu's habitus the role it gave to domination. The cultural approach broke with functionalism and went deeper into the analysis of communication, the role of imaginaries and the social institution of the World, which explains its grasp on today problems.